2013
DOI: 10.1016/j.ijheatmasstransfer.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of concrete fracture on the rain infiltration and thermal performance of building facades

Abstract: Postprint: Rouchier S., Woloszyn M., Foray G., Roux J.-J., 2013. Influence of concrete fracture on the rain infiltration and thermal performance of building facades, International Journal of Heat and Mass Transfer vol. 61, pp. 340-352. DOI: 10.1016/j.ijheatmasstransfer.2013.02.013 Abstract Water infiltration is known to play an important part in the degradation process of construction materials. Over time, microscopic and macroscopic cracks progressively develop under the effects of mechanical loading and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The physical model for the simulation is the system of partial differential equations for coupled heat and moisture transfer, written here with the temperature T and the vapour pressure p v as driving potentials. These conservation equations follow the notations and hypotheses usually made in building physics applications [11,17,30]. For the sake of simplification, liquid transfer is not considered.…”
Section: Theory and Problem Formulation 21 Forward And Inverse Problemsmentioning
confidence: 99%
“…The physical model for the simulation is the system of partial differential equations for coupled heat and moisture transfer, written here with the temperature T and the vapour pressure p v as driving potentials. These conservation equations follow the notations and hypotheses usually made in building physics applications [11,17,30]. For the sake of simplification, liquid transfer is not considered.…”
Section: Theory and Problem Formulation 21 Forward And Inverse Problemsmentioning
confidence: 99%
“…The liquid flow from the rain can vary according to the wind speed [5]. In the literature [17,19,22,39], it is possible to find values within the range [ 2 · 10 −5 , 8 · 10 −4 ] kg/(m 2 · s) . Simulations were performed using the bvp4c, with relative and absolute tolerances of the solver set to 10 −5 .…”
Section: Applicationmentioning
confidence: 99%
“…Neglecting the variation of the capillary pressure and the mass content with temperature [23], the partial derivative of P c can be written as:…”
Section: B)mentioning
confidence: 99%
“…The Euler and Crank-Nicolson implicit schemes have been used in many studies and implemented in building simulation tools, as reported in the literature [2,9,13,14,16,18,23,24,27], due to their numerical property of unconditional stability. Nevertheless, at every time step, one has to use a tridiagonal solver to invert the linear system of equations to determine the solution value at the following time layer.…”
Section: Introductionmentioning
confidence: 99%